The characteristics and regional distribution of older workers in Portugal - Lopes, João Carlos (2012)
Population ageing is a common trend in most developed countries with many important economic, social and political consequences. In Portugal, this trend has been particularly strong. The ageing index was 34% in 1970, it is about 129% in 2011, according to the provisory results of the last Census and most recent demographic projections, is expected to be over 240% in 2030. One of the main issues associated with ageing is its effect on the composition of the labour force. The main purpose of this paper is to study the changes in the age structure of the Portuguese labour force between 1989 and 2009. First of all, the size and relative weight of older workers are quantified, both as a group (people with more than 54 years old), by age sub-groups (55-59; 60-64; 65 +) and gender. Then, particular attention is given to the regional distribution of these workers, both at the Nuts II (7 regions) and Nuts III (30 regions) levels. The sectoral distribution is also measured, at national and regional levels. Finally, a comparative analysis is made between younger and olderer workers, considering the education levels, establishments’ size, labour compensation and part-time versus full time work regime. The main data used are Quadros de Pessoal, from Ministry of Solidarity and Social Security covering people working in the private business sector (around 3,3 million workers, in 2009) and excluding liberal professionals.